DIGITALISASI ILMU KEISLAMAN SEBAGAI SOLUSI KETERBATASAN INFRASTRKTUR KEAGAMAAN DI DENPASAR BALI - ImroatunShaleha (Al Naqdu, 2024)
Type the Islamic knowledge is a foundation in determining the way of life of every human being in the world. So every human being is required to seek knowledge, as Allah has explained in Q.S At-Taubah Yat 122 the obligation to seek knowledge. As one of the phenomena that exist in Denpasar, Bali, which is a population with a world bustle, and coupled with the majority of the population are private workers. Whose activities are always busy and are rarely at home, this causes limited visits to attend assemblies of religious knowledge. So as an alternative, it is necessary to improve infrastructure and digitize Islamic knowledge, in order to streamline and facilitate the people in Denpasar, Bali in accessing religious lectures. As for this research, this type of research uses qualitative research by explaining a phenomenon in more detail. So the formulation of the problem from this research is how do Muslim communities in Bali access Islamic knowledge in the midst of limited religious infrastructure, especially in Denpasar, Bali? To answer these problems the researcher divides and describes the answers into three discussions, including: 1) the meaning of Islamic knowledge; 2) Limited Infrastructure and Human Resources (HR); 3) Digitalization Solutions.